Mice with lung airway ciliopathy develop persistent Mycobacterium abscessus lung infection and have a proinflammatory lung phenotype associated with decreased T regulatory cells - Nava, Audrey; Hahn, Andrew C.; Wu, Terry H.; Byrd, Thomas F. (Frontiers in Immunology, 2022)
Introduction Human pulmonary infection with non-tuberculous mycobacteria (NTM) such as Mycobacterium abscessus (Mabs) occurs in seemingly immunocompetent patients with underlying structural lung disease such as bronchiectasis in which normal ciliary function is perturbed. In addition to alterations in mucociliary clearance, the local immunologic milieu may be altered in patients with structural lung disease, but the nature of these changes and how they relate to NTM persistence remain unclear. Methods We used a mouse strain containing a conditional floxed allele of the gene IFT88, which encodes for the protein Polaris. Deletion of this gene in adult mice reportedly leads to loss of cilia on lung airway epithelium and to the development of bronchiectasis. In a series of experiments, IFT88 control mice and IFT88 KO mice received different preparations of Mabs lung inocula with lung CFU assessed out to approximately 8 weeks post-infection. In addition, cytokine levels in bronchoalveolar lavage (BAL) fluid, lung T cell subset analysis, and lung histopathology and morphometry were performed at various time points. Results Mabs embedded in agarose beads persisted in the lungs of IFT88 KO mice out to approximately 8 weeks (54 days), while Mabs agarose beads in the lungs of IFT88 control mice was cleared from the lungs of all mice at this time point. T cells subset analysis showed a decrease in the percentage of CD4+FoxP3+ T cells in the total lymphocyte population in the lungs of IFT88 KO mice relative to IFT88 control mice. Proinflammatory cytokines were elevated in the BAL fluid from infected IFT88 KO mice compared to infected IFT88 control mice, and histopathology showed an increased inflammatory response and greater numbers of granulomas in the lungs of infected IFT88 KO mice compared to the lungs of infected IFT88 control mice. Scanning lung morphometry did not show a significant difference comparing lung airway area and lung airway perimeter between IFT88 KO mice and IFT88 control mice. Discussion Persistent lung infection in our model was established using Mabs embedded in agarose beads. The utility of using IFT88 mice is that a significant difference in Mabs lung CFU is observed comparing IFT88 KO mice to IFT88 control mice thus allowing for studies assessing the mechanism(s) of Mabs lung persistence. Our finding of minimal differences in lung airway area and lung airway diameter comparing IFT88 KO mice to IFT88 control mice suggests that the development of a proinflammatory lung phenotype in IFT88 KO mice contributes to Mabs lung persistence independent of bronchiectasis. The contribution of cilia to immune regulation is increasingly recognized, and our results suggest that ciliopathy associated with structural lung disease may play a role in NTM pulmonary infection via alteration of the local immunologic lung milieu.